Cognitive mechanisms underlying virtual reality exposure's efficacy in the treatment of arachnophobia - Cote, Sophie (University of Ottawa (Canada), 2006)
Virtual exposure therapy for phobias is a growing field of interest. Studies have begun to demonstrate its efficacy, which is probably equivalent to traditional in vivo exposure. However, although a majority of studies addressed treatment efficacy itself, few have attempted to understand its mechanisms. In the case of traditional therapy for phobias, two models are still the object of strong debate: the information processing model and the perceived self-efficacy model. Interestingly, the debate among the supporters of these models is still fuelled by their attempts to prove the predictive superiority of their own model by using predicted variables that are in fact different. No study has yet compared directly the most likely predictors of change, either for in vivo or for in virtuo exposure. The goal of this thesis was to contrast the predictive value of different treatment mechanisms for specific phobias with a therapy using virtual reality exposure. The hypotheses are the following: general improvement (as measured by the Fear of Spiders Questionnaire) will be significantly predicted by changes in process variables such as perceived self-efficacy, beliefs and the emotional Stroop task, changes in information processing (as measured with the pictorial Stroop task) will better predict changes in anxiety during a Behavioural Avoidance Test (BAT), while changes in perceived self-efficacy will better predict changes in avoidance behaviours during a BAT. Twenty-eight adults suffering from arachnophobia were assessed for standardized inclusion and exclusion criteria. General outcome and specific processes measures included various questionnaires, a pictorial Stroop task and a BAT . The avoidance behaviour was measured by the participants' capacity to approach a live tarantula during the BAT. Anxiety was measured by recording participants' heart rate as they looked at the tarantula during the first minute of the BAT. All measures were completed before treatment (session 1) and at post-treatment (session 7). After explanations about the cognitive-behavioural rationale for the treatment of phobias and an initiation to the virtual reality equipment (session 2), participants went through virtual exposure for five sessions (of 60 minutes each) in various virtual environments with spiders. During the last session, a discussion about relapse prevention took place. (Abstract shortened by UMI.)
Keywords: Psychology, Clinical.